A planar wideband inductively coupled feed patch antenna for UHF RFID tag - Bashri, M. S. R.; Ibrahimy, Muhammad Ibn; Motakabber, S. M. A. (2013)
A planar wideband patch antenna for ultrahigh frequency (UHF) radio frequency identification (RFI D) tag for metallic applications is presented in this research work. Three different shape patches are inductively coupled to a triangle loop to excite three resonances close to each other to f orm wide impedance bandwidth for universal application UHF ( 860960 MHz) RFID. The structure of the proposed antenna ex hibits planar profile to provide ease of fabrication for c ost reduction well suited for mass production. The simulation of the antenna was carried out using Finite Element Method (FEM) b ased software, Ansoft HFSS v13. The performance of the d esign was verified by the simulation and measurement results which show good agreement. The simulated and measured impedanc e bandwidth of 113 MHz and 117 MHz (return loss ≥ 6 d B) was achieved to cover the entire UHF RFID operating fre quency band worldwide.